Cuff-Based Oscillometric Central and Brachial Blood Pressures Obtained Through ABPM are Similarly Associated with Renal Organ Damage in Arterial Hypertension - Patricia Fernández-Llama; Júlia Pareja; Sergi Yun; Susana Vázquez; Anna Oliveras; Pedro Armario; Pedro Blanch; Francesca Calero; Cristina Sierra; Alejandro de la Sierra (Karger Publishers, 2017)
Background/Aims: Central blood pressure (BP) has been suggested to be a better estimator of hypertension-associated risks. We aimed to evaluate the association of 24-hour central BP, in comparison with 24-hour peripheral BP, with the presence of renal organ damage in hypertensive patients. Methods: Brachial and central (calculated by an oscillometric system through brachial pulse wave analysis) office BP and ambulatory BP monitoring (ABPM) data and aortic pulse wave velocity (PWV) were measured in 208 hypertensive patients. Renal organ damage was evaluated by means of the albumin to creatinine ratio and the estimated glomerular filtration rate. Results: Fifty-four patients (25.9%) were affected by renal organ damage, displaying either microalbuminuria (urinary albumin excretion ≥30 mg/g creatinine) or an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2. Compared to those without renal abnormalities, hypertensive patients with kidney damage had higher values of office brachial systolic BP (SBP) and pulse pressure (PP), and 24-h, daytime, and nighttime central and brachial SBP and PP. They also had a blunted nocturnal decrease in both central and brachial BP, and higher values of aortic PWV. After adjustment for age, gender, and antihypertensive treatment, only ABPM-derived BP estimates (both central and brachial) showed significant associations with the presence of renal damage. Odds ratios for central BP estimates were not significantly higher than those obtained for brachial BP. Conclusion: Compared with peripheral ABPM, cuff-based oscillometric central ABPM does not show a closer association with presence of renal organ damage in hypertensive patients. More studies, however, need to be done to better identify the role of central BP in clinical practice.